Ecosystem service approach for community-based management towards sustainable blue economy - K, GREEN SEA; M, RAJAKUMAR; T, UMAMAHESWARI; N V, SUJATH KUMAR; P, JAWAHAR; KEER, NARESH RAJ; YADAV, RAJPAL (The Indian Journal of Animal Sciences, 2022)
The present study was undertaken to examine the role of community-based fishers in blue economy taking ecosystem and livelihood development and sustainability of Gulf of Mannar, Tamil Nadu, India. A questionnaire was designed to capture context-specific community-based blue economy practices. The virtual factors and environmental determinants which affect the sustainability of ecosystem between resource benefitters were evaluated. A significant difference is noticed between male and female beneficiaries for preference to all the variables except enhanced waste management practices variable (insignificant difference- 0.183; Mann-Whitney U test). All the variables significantly advance the livelihood sustainability of ecosystem-dependent population and the ecosystem service evaluation process. The present survey also resulted that the better sustainability of blue economy involved the significant implementation of growth agendas by minimizing the effluent and sewage disposal, developmental activities in industrial areas, disaster outbreak and eliminating harmful fishing practices, overfishing and instead incentivizing approaches that promote growth, improve conservation, build sustainable fisheries, and terminate the IUU (illegal, unreported and unregulated) fishing. An ecosystem-based management framework, improved governance is required to grow and improve the sustainability of livelihood and ecosystem towards a blue economy. Innovative financing to direct investments into economic activities is also needed to enhance ocean health. A further step would be to assess how such human inputs or improved management practices could be included in the set of ecosystem service indicators.